Motivación y desempeño por competencias de los colaboradores de la asociación civil proyecto amazonas en Iquitos año 2023 - Luque Lancha, Alexis Xavier (2023)
The general objective was established to determine the relationship between motivation and performance by competencies of the Amazon Project Civil Association in Iquitos in 2023, this research was of an applied type, of a non-experimental design, where the population and study sample at 30 collaborators, who were the main source to know their perception through a survey. Therefore, it was concluded that the level of motivation is qualified as medium, this is because employees sometimes work harder when they receive specific feedback for the performance; sometimes they try to project a favorable image of the social relationships; as they also sometimes strive to gain great mastery of their work and personal growth; but they always assume responsibility and use the authority that gives them prestige before others. Regarding the level of performance by competence, it is qualified as high, since the orientation to results is the most developed competence; it also almost always meets quality objectives; Furthermore, half the time he understands and promotes the decisions made by the organization; and half the time it shows that your work has a purpose. In general terms, it was determined that there is a significant relationship between the variables corroborated by a coefficient and sig of (r=0.780; p=0.000).